2020
DOI: 10.1136/bcr-2020-238302
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus schleiferidiabetic foot osteomyelitis and bacteraemia in an immunocompromised host

Abstract: Staphylococcus schleiferi is a Gram-positive coccus bacterium first discovered in 1988 that is typically associated with skin and ear infections in dogs, cats and birds. It is infrequently described as a human pathogen. There are, however, emerging reports of S. schleiferi infections in diverse clinical scenarios in humans, particularly in patients with weakened immune systems. S. schleiferi may be underrecognised due to limitations in routine microbiology diagnostic protocols and mislabelling as other Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Similarly a rare case of S. schleiferi causing diabetic foot osteomyelitis and bacteremia was reported by Nguyen and team in an immunocompromised patient [ 6 ]. The patient was initially reported to have grown Staphylococcal epidermidis which was later rectified as S. schleiferi on day 5 and treated with broad-spectrum antibiotics later de-escalated to piperacillin-tazobactam and subsequently to ceftriaxone for a total duration of six weeks [ 6 ]. The case we reported was treated initially with vancomycin and meropenem, later de-escalated to cefazolin and clindamycin based on culture and sensitivity report.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Similarly a rare case of S. schleiferi causing diabetic foot osteomyelitis and bacteremia was reported by Nguyen and team in an immunocompromised patient [ 6 ]. The patient was initially reported to have grown Staphylococcal epidermidis which was later rectified as S. schleiferi on day 5 and treated with broad-spectrum antibiotics later de-escalated to piperacillin-tazobactam and subsequently to ceftriaxone for a total duration of six weeks [ 6 ]. The case we reported was treated initially with vancomycin and meropenem, later de-escalated to cefazolin and clindamycin based on culture and sensitivity report.…”
Section: Discussionmentioning
confidence: 71%
“…The patient reported by Yarbrough et al was treated with intravenous vancomycin and later de-escalated to ceftriaxone for 6 weeks with complete resolution and no adverse clinical progression [7]. Similarly a rare case of S. schleiferi causing diabetic foot osteomyelitis and bacteremia was reported by Nguyen and team in an immunocompromised patient [6]. The patient was initially reported to have grown Staphylococcal epidermidis which was later rectified as S. schleiferi on day 5 and treated with broad-spectrum antibiotics later de-escalated to piperacillin-tazobactam and subsequently to ceftriaxone for a total duration of six weeks [6].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Routine microbiology diagnostic protocols may misidentify S. schleiferi as S. aureus due to their similarity. A few case reports in humans illustrate the pathogenicity and virulence of S. schleiferi [ 4 ]. Exposure to infected dogs as a source of infection was in the majority of those reports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Culturomic and metagenomic approaches revealed that DFU and DFOM ecology is established by a predominance of Firmicutes and particularly Staphylococus aureus and coagulase-negative Staphylococcus (CoNS) [ 7 , 8 , 9 ]. While S. aureus is clearly implicated in the unfavourable course of these wounds [ 10 ], the role of CoNS in infected DFUs remains poorly understood, even though their pathogenicity has been reported [ 11 , 12 , 13 , 14 ]. Twelve of the fifty CoNS species, including Staphylococcus lugdunensis , Staphylococcus saprophyticus, Staphylococcus schleiferi and Staphylococcus epidermidis , have been identified as true pathogens and are at the origin of endogenous or nosocomial infections involving bacteremia, pneumonia, urinary tract infection, wound infection and osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%